2020
DOI: 10.1002/jmv.26571
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, epidemiological, and molecular aspects of picornaviruses (entero, parecho) in acute gastroenteritis: A study from Pune (Maharashtra), Western India

Abstract: Among enteric viruses, rotavirus A (RVA), norovirus (NoV), adenovirus, and astrovirus (AstV) are the major etiological agents associated in acute gastroenteritis. The present study highlights, clinical, epidemiological, and molecular aspects with respect to RVA, NoV, enterovirus (EV), and human parechovirus (HPeVs) in sporadic cases (n = 305) of acute gastroenteritis, Pune (Maharashtra), Western India. Detection of RVA was carried out by enzyme‐linked immunosorbent assay, NoV, EV, and HPeVs by reverse transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
6
1
Order By: Relevance
“…In a recent study on global genotype trends among children with norovirus gastroenteritis, GII.4 Sydney[P16] and GII.4 Sydney[P31] viruses comprised more than 50% of the strains 30 . In our study, GI viruses were detected in 10.2% of the norovirus positive cases, which is higher than reported in other studies from India 8–12,19 …”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…In a recent study on global genotype trends among children with norovirus gastroenteritis, GII.4 Sydney[P16] and GII.4 Sydney[P31] viruses comprised more than 50% of the strains 30 . In our study, GI viruses were detected in 10.2% of the norovirus positive cases, which is higher than reported in other studies from India 8–12,19 …”
Section: Discussioncontrasting
confidence: 65%
“…Globally, GII.4 noroviruses are the most frequently detected genotype 4 . There are few reports on the disease burden of noroviruses among children less than 5 years of age in India; these range from 1.2% to 15.1%, depending on the setting which includes hospital‐based, community‐based, or in a birth cohort setting 8–13 . There are no studies describing norovirus disease burden in rotavirus vaccinated children after the introduction of rotavirus vaccine into the Universal Immunization Program (UIP) in India in 2016 14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final dataset included data on young people aged less than 18 years from 18 countries (Thailand, Spain, Korea, Japan, China, Iran, Pakistan, Turkey, Bulgaria, Italy, India, Germany, Ethiopia, Nigeria, Bangladesh, United States, Ghana, and Russia). Amidst the included studies, 33 were cross‐sectional in study design, of which 31 were case‐only 17–20,24,41–66 and 2 presented data for healthy individuals 25,67 . Thirty‐three cross‐sectional studies comprised 17,226 paediatric patients with gastroenteritis and 277 children without gastroenteritis.…”
Section: Resultsmentioning
confidence: 99%
“…The epidemiology of PeV‐A14 is poorly understood, but it has been reported in stool samples from healthy children and patients with acute gastroenteritis in China, 6 Thailand, 14 Malawi, 18 and India, 19 among other countries. A study of stool samples from children with acute gastroenteritis in Thailand reported that PeV‐A14 was the third‐most‐prevalent PeV‐A genotype 14 .…”
Section: Discussionmentioning
confidence: 99%